Phylogenetic, morphological and biochemical studies on Thermospirulina andreolii gen. & sp. nov. (Cyanophyta) from the Euganean Thermal District (Italy). Issue 5 (3rd September 2021) - Moro, Isabella; Fuiano, Maria Alessia; Rascio, Nicoletta; De Philippis, Roberto; La Rocca, Nicoletta
ABSTRACT: The therapeutic muds of the Euganean Thermal District, the oldest and largest thermal site in Europe, are recognized by the Italian Health System as an excellent treatment for osteoarticular diseases of inflammatory origin. The beneficial effects that have been demonstrated for these muds are due not only to heat and electrolytes, but also to bioactive compounds released from the microbial community, mainly composed of cyanobacteria, living in the thermal mud surface. We isolated and characterized a new coil-shaped filamentous cyanobacterium through a polyphasic approach. Molecular, morphological and biochemical data supported the description of the microorganism as a new species, Thermospirulina andreolii, of the new genus Thermospirulina, which includes other Spirulina -like cyanobacteria living in different thermal springs around the world. Biochemical analyses highlighted the capability of the strain to synthesize high amounts of phycocyanin and exopolysaccharides, with possible antioxidant and anti-inflammatory activities, suggesting its potential for contributing to the healing properties of the Euganean muds.